A NOTE ON QUASI SPLIT NULL POINT FEASIBILITY PROBLEMS - Moudafi, A. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
Inspired by the very recent work by M.-A. Noor and Kh.-I Noor [9] and given a closed convex set-valued mapping C, we propose a split algorithm for solving the problem of finding an element x^* in C(x^*) such that its image, Ax^*, under a linear operator, A, is a zero of a given maximal monotone operator T in Hilbert spaces setting. Then, we present a strong convergence result and state some examples as applications.